2021
DOI: 10.1617/s11527-021-01650-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basalt micro-fibres on the abrasion resistance of concrete in hydraulic structures

Abstract: In hydraulic structures, abrasion resistance can be a significant driver in concrete specification. Basalt micro-fibres represent a potentially sustainable construction product and have been shown to provide various benefits in concrete, however the implications for hydrodynamic abrasion resistance are to date unclear. This paper is the first investigation of its kind to examine the abrasion resistance of basalt fibre-reinforced (BFR) concretes using the ASTM C1138 underwater test method. Towards this, concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Li et al 14 conducted an experimental study and concluded that basalt fibers would reduce the compressive strength, tensile strength and flexural strength of concrete, while the addition of alkali‐resistant basalt fibers had an improving effect on the compressive strength, tensile strength and flexural strength. Omoding et al 15 reported that the basalt fiber content up to 3 kg/m 3 had no significant effect on the compressive strength, splitting tensile strength, elastic modulus, and wear resistance of concrete. Li et al 16 concluded that the addition of basalt fibers increased the total porosity and pore volume of concrete but decreased the average pore size, suggesting that basalt fiber could refine the pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 14 conducted an experimental study and concluded that basalt fibers would reduce the compressive strength, tensile strength and flexural strength of concrete, while the addition of alkali‐resistant basalt fibers had an improving effect on the compressive strength, tensile strength and flexural strength. Omoding et al 15 reported that the basalt fiber content up to 3 kg/m 3 had no significant effect on the compressive strength, splitting tensile strength, elastic modulus, and wear resistance of concrete. Li et al 16 concluded that the addition of basalt fibers increased the total porosity and pore volume of concrete but decreased the average pore size, suggesting that basalt fiber could refine the pore structure.…”
Section: Introductionmentioning
confidence: 99%